Genetic Variation Within Four Captive Chital (Axis axis) Populations in Indonesia - Muhammad Zulfiqar Meizar Pratama; Zuliyati Rohmah; Tuty Arisuryanti (Universitas Gadjah Mada, 2023)
Chital is a native animal from South Asia. Chital had been introduced to many countries, including Indonesia. Chital was first introduced to Indonesia in 1811 at Bogor Palace and since had been kept captive around Indonesia. Currently, no research had been done concerning the genetic variation of Indonesian chital. Therefore, the purpose of this research was to analyze genetic variation and phylogenetic relationship of chital from Pusat Inovasi Agroteknologi Universitas Gadjah Mada (PIAT UGM), Prambanan Temple, Gembira Loka Zoo, and Bogor Palace, based on mitochondrial D-loop fragment. This study used a Polymerase Chain Reaction (PCR) method. DNA was extracted from faecal samples and amplified with L15995 and H16498 primers. The analysis used for this research were genetic variations, haplotype networking, and phylogenetic relationships between populations. This study detected 5 haplotypes out of 20 sequences with 10 polymorphic sites and 2 indels. The haplotype diversity and the nucleotide diversity were 0.443 and 0.002 respectively, and the genetic distance was between 0 and 2.03% (average 0.55%). This research also showed one main haplotype, labelled as haplotype 1, which consisted of all individuals from PIAT and Prambanan Temple, four individuals from Bogor Palace, and one individual from Gembira Loka. This grouping proves that the majority of chital population in Indonesia came from Bogor Palace. One individual from Gembira Loka has a considerable genetic divergence from the rest of the samples, which might indicate it originated from a different source population.